NIAT UNTUK TINGGAL ATAU KEMBALI? MOTIVASI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PERAWAT INDONESIA BEKERJA DI JEPANG - Susi Mariani Harahap; Tedi Gunawan (Parahyangan Center for International Studies, 2022)
In 2008, Japan agreed to recruit Indonesian nurses to work as nurses as a part of the Indonesia-Japan Economic Partnership Agreement (IJEPA). This study aimed to explore the motivation behind working in Japan and factors behind the Indonesian nurses' intention to stay in Japan or return to Indonesia after the contract is terminated. This descriptive quantitative study used an online survey involving 103 respondents. Results revealed that a high rate of remuneration and better working environment were the pull factors whereas low salarie, and poor working conditions in Indonesia were the major reasons why Indonesian nurses wanted to work in Japan. Of the 103 respondents, 71 % stated that they intended to remain in Japan, whereas 29 % preferred to return to Indonesia after the contract is terminated. The research only focused on one framework of Indonesian migrant workers (nurse). At the end, hopefully this research can be a comprehensive discussion of Indonesian nurse workers and enrich the study of international migration.